DEVELOPMENT OF THE ABILITY TO DELIVER ACTIVE LEARNING INSTRUCTION OF ELEMENTARY SCHOOL STUDENTS TEACHERS THOUGH COACHING - Urabunnualchat, Wilaphan; Homchaiyawong , Dounghathai; Kitroongrueng, Poranat (Journal of MCU Phetchaburi Review, 2023)
This research aimed to 1) develop elementary school student teachers’ ability to deliver active learning instruction, 2) explore the elementary school student teachers’ satisfaction with coaching, and 3) explore elementary school students’ satisfaction with the instruction delivered by the elementary school student teachers. The research design was quasi experimental research. Data was collected from target populations, consisting of 1) twenty 5th-year elementary school student teachers undergoing teacher profession training in the second semester of the academic year 2022, who were voluntarily sampled, 2) three university supervisors, who were purposively sampled with some criteria, as follows: having knowledge and experience in elementary education, teaching, supervising, and volunteering to be involved in the development; and 3) students under the responsibility of the elementary school student teachers. The research instruments as are follows: a coaching plan, a satisfaction survey for the elementary school student teachers to evaluate their satisfaction with the coaching process, and a satisfaction survey for the elementary school students to evaluate their satisfaction with the student teachers’ instruction. The data analysis was conducted using mean (x̅), standard deviation (S.D.), t-test for dependent, and content analysis. The findings are as follows: 1) the post-coaching elementary school student teachers’ ability to deliver active learning instruction was higher than their pre-coaching ability at a statistically significant level of .01; 2) the elementary school student teachers’ satisfaction with the coaching process was at a high level; and 3) the elementary school students’ satisfaction with the instruction delivered by the student teachers was at a high level.